Church of Saint Benedict (São Paulo, Brazil): memory, heritage and orality through Sônia Gabriel’s perspective: Church of Saint Benedict (São Paulo, Brazil): memory, heritage and orality through Sônia Gabriel’s perspective (Revista de História da UEG (REVHIST), 2025)
This article aims to analyze the relationship between memory, heritage, and orality through the study of the Church of Saint Benedict, located in São José dos Campos (SP). The research adopts a qualitative bibliographic review as its methodology, having as its main reference the work “Mistérios do Vale”, by Sônia Gabriel. The study draws from popular narratives associated with the temple — such as the presence of a body within its walls or the existence of underground tunnels — articulating them with specialized literature on tangible and intangible heritage. The findings show that the city's memories remain alive through local orality. This research contributes to the debate on cultural heritage and subaltern memory in the urban context, proposing a historiographical listening that is attentive to voices excluded from official history.Keywords: Church of Saint Benedict. Oral History. City. Heritage.
Keywords: Church of Saint Benedict; Oral History; City; Heritage